A Case Study of the Phenotypic Variations in Barilius Bendelisis (Hamilton) from a Perennial Stream and a Fish Pond of Garhwal Himalayan Region of Uttarakhand, India - Pranav Singh; Shivani Nautiyal; Navneet Swami; Jitendra Singh Rana; Manju Prakash Gusain; Om Prakash Gusain (Journal of Tropical Life Science, 2020)
A comparative study on the morphometric and meristic variables of Barilius bendelisis (Ham.) from two different water bodies, i.e., Khanda Gad, a perennial spring fed stream and fish pond in the Garhwal Himalayan region of Uttarakhand was made during the present study. A total of 100 specimens were analysed for 26 different morphometric variables and 14 meristic counts. The majority of morphometric variables showed linear relationship when expressed in relation to total length and head length, whereas meristic counts remained constant with increasing body length. Standard length was found to be the highly correlated character in samples from both sites. Principal Component Analysis of 10 significant morphometric variables yielded three components accounting for 73.38% of the total variation. Principal Component Analysis of 3 meristic variables yielded single component accounting for 62.3% of total variation. Discriminant Function Analysis for morphometric and meristic variables showed that 98% and 83% of individuals were allocated into their original populations respectively. The cluster analysis for morphometric characters showed of fish populations from both sites formed two major clades, thus significantly differentiating the two stocks of fish population.